Severe jaundice due to coexistence of Dubin-Johnson syndrome and hereditary spherocytosis: A case report - Uğur KORKMAZ,; Ali Erkan DUMAN,; Deniz ÖĞÜTMEN KOÇ,; Yeşim Gürbüz,; Gökhan Dindar,; Fatih ENSAROĞLU,; Selçuk Yusuf ŞENER,; Ömer ŞENTÜRK,; Sadettin HÜLAGÜ, (Turkish Journal of Gastroenterology, 2019)
-